Antimicrobial activity of different types of Centella asiatica extracts against foodborne pathogens and food spoilage microorganisms - Suzita Ramli (Tanjung Malim, 2021)
Antimicrobial activity of different types of Centella asiatica extracts against foodborne pathogens and food spoilage microorganisms by Suzita Ramli